Microencapsulation of beta-galactosidase with different biopolymers by a spray-drying process - Berta N. Estevinho (2014)
The aim of this work was to investigate the possibility of producing microparticles containing beta-galactosidase, using different biopolymers (arabic gum, chitosan, modified chitosan, calcium alginate and sodium alginate) as encapsulating agents by a spray-drying process. This study focused on the enzyme beta-galactosidase, due to its importance in health and in food processing. Encapsulation of beta-galactosidase can increase the applicability of this enzyme in different processes and applications. A series of beta-galactosidase microparticles were prepared, and their physicochemical structures were analyzed by laser granulometry analysis, zeta potential analysis, and by scanning electron microscopy (SEM). Microparticles with a mean diameter around 3 mu m have been observed, for all the biopolymers tested. The microparticles formed with chitosan or arabic gum presented a very rough surface; on the other hand, the particles formed with calcium or sodium alginate or modified chitosan presented a very smooth surface. The activity of the enzyme was studied by spectrophotometric methods using the substrate ONPG (O-nitrophenyl-beta,D-galactopyranoside). The microencapsulated beta-galactosidase activity decreases with all the biopolymers. The relative enzyme activity is 37, 20, 20 and 13%, for arabic gum, modified chitosan, calcium alginate and sodium alginate, respectively, when compared with the free enzyme activity. The enzyme microparticles formed with arabic gum shows the smallest decrease of Vmax, followed by the calcium alginate, sodium alginate, and modified chitosan.